Development and Evaluation of Nutraceutical Tablets from Selected Plant Extracts: A Novel Approach to Functional Medicine (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The potential of a seed powder blend made of Cucumis melo, Punica granatum, and Linum usitatissimum in a 1:1:1 ratio is investigated in this study. In order to guarantee a consistent particle size distribution (10–30 µm), the seeds were ground into a fine powder. The parameters of bulk powder showed strong cohesion and poor flow ability. Photo microscopy, however, showed fibrous, capsular structures that were perfect for formulation. Significant growth of Lactobacillus acidophilus and Bifidobacterium bifidum indicated that the mix had superior prebiotic potential compared to individual seed powders and the conventional chicory powder. It also showed remarkable antioxidant activity. Studies on animals verified the blend's effectiveness and safety. A 40-day feeding trial in Albino Wistar rats demonstrated its haematinic effects, raising haemoglobin levels from 12.1% to 16.5% and red blood cell counts from 7.46 to 9.55 million/mm³. Acute toxicity trials revealed no negative effects. Additionally, the combination decreased VLDL and triglycerides and raised serum protein levels, suggesting possible cardiovascular advantages. Its safety for those with diabetes is supported by the fact that blood glucose levels stayed within the usual range.The product, which was made as capsules, complied with pharmacopoeial requirements for disintegration time and weight variation. A shelf life of nine to twelve months is suggested by stability studies conducted under accelerated settings. Over the course of three months, the blend's prebiotic activity stayed steady, maintaining its capacity to promote probiotic growth. This nutraceutical formulation is a good option for treating anemia, malnutrition, and metabolic disorders since it provides a promising blend of antioxidant, prebiotic, and health-promoting qualities.